The effect of demographic factors on environmental knowledge among university students - Akhmad Sukri; Muhammad Arief Rizka; Hadi Gunawan Sakti; Marheny Lukitasari; Elly Purwanti (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study explored and revealed the demographic factors that influence students' environmental knowledge (EK) in Indonesia. This survey research involved 1,345 students from 15 universities across Indonesia. The research employed a validated questionnaire on EK and was modified to match the circumstances in Indonesia. The instrument consisted of six statements with five scales namely 1=strongly disagree, 2=disagree, 3=indifferent, 4=agree, and 5=strongly agree. Five demographic variables were tested together to determine their effect on students' EK. Descriptive analysis, analysis of variance (ANOVA), and multiple linear regression were used to test the independent variables. The result of the study revealed that gender, study program, grade point average (GPA), and parents’ occupation variable have an effect simultaneously on students' EK (p<.05) with a contribution of 6.2% (R square=.062), while the students’ grade variable has no effect on EK (p>.05). Female students have better EK than male students (p<.05). The trend showed that the higher the GPA, the higher the EK of the student (p<.05). Hence, the trend showed that students whose parents have lower income tend to have better EK than those whose parents have higher income. Students in science education and computer course have better EK than science, non-science education, and social humanities study programs. This study implicated the importance of introducing environmental insights through education to increase students' EK in higher education.